EVALUATING THE RELATIONSHIP BETWEEN INTERNATIONAL TOURISM RECEIPTS, REAL EXCHANGE RATES, AND ECONOMIC GROWTH: A CASE STUDY OF THE GAMBIA - Jallow, Kaddijatou B (Jurnal Ilmiah Mahasiswa FEB, 2022)
This study aims to evaluate and determine the association between tourism receipts, real exchange rate as independent variables, and gross domestic product (GDP) as dependent variable implementing time-series data from 1996 to 2018 yearly of The Gambia in international tourism. In addition, econometric approaches such as OLS to determine the influence of international tourism receipts on GDP in The Gambia and the effects of the real exchange rate on the country's gross domestic products. The outcome shows international tourism receipts have a positive relationship to GDP at 5% level with (3.64) of coefficient the exchange rate is (-2.89) of coefficient negatively related to GDP at 5% level. The Johansen cointegration, Granger causality, and VEC test the association between international tourism receipts, real exchange rate, and GDP in the Gambia. The results indicated one cointegration relationship and showed no long-run causality from INT_RCPT and REER to GDP. There is short-run causality running from GDP and exchange rate to international tourism receipts in The Gambia. The results of Granger causality show entirely all variables do not cause each other.Keywords: International Tourism Receipt, Real Exchange Rate, GDP, OLS, Cointegration, Granger Causality, and Gambia